Process Equipment Procurement in the Chemical and Related Industries - Golwalkar, Kiran (Springer International Publishing : Imprint: Springer, 2015)
This concise volume explains when to procure new equipment, how to prepare specifications for floating inquiries, and provides guidelines for detailed technical discussions with vendors in the chemical industry and related industries. It covers the common equipment and supplies used in chemical plants and effluent treatment facilities such as pumps, blowers, reactors, heat exchangers, waste heat recovery boilers, and heat and acid resistant lining. This book serves as a checklist to the plant managements for procurement of the correct equipment in the most efficient timeframe ensuring that projects are not delayed due to the long time period required for procurement of new equipment. This book also: · Provides students and engineers just entering industry good practical knowledge of equipment and machinery before they assume responsibilities in chemical plants · Maximizes readers' understanding to pose the best inquiries to engineers, plant managers, and product vendors when acquiring industrial equipment and supplies · Facilitates plant QA officers' conversance with the lifecycles of a plant's equipment and maintenance intervals.